Powerlessness Also Corrupts: Lower Power Increases Self-Promotional Lying - Li, Huisi (Jessica); Chen, Ya-Ru; Hildreth, John Angus D. (Organization Science, 2023)
The popular maxim holds that power corrupts, and research to date supports the view that power increases self-interested unethical behavior. However, we predict the opposite effect when unethical behavior, specifically lying, helps an individual self-promote: lower rather than higher power increases self-promotional lying. Drawing from compensatory consumption theory, we propose that this effect occurs because lower power people feel less esteemed in their organizations than do higher power people. To compensate for this need to view themselves as esteemed members of their organizations, lower power individuals are more likely to inflate their accomplishments. Evidence from four studies supports our predictions: compared with those with higher power, executives with lower power in their organizations were more likely to lie about their work achievements (Study 1, n = 230); graduate students with lower power in their Ph.D. studies were more likely to lie about their publication records (Study 2, n = 164); and employees with lower power were more likely to lie about having signed a business contract (Studies 3 and 4). Mediation analyses suggest that lower power increased lying because lower power individuals feel lower esteem in their organizations (Study 3, n = 562). Further supporting this mechanism, a self-affirmation intervention reduced the effect of lower power on self-promotional lying (Study 4, n = 536). These converging findings show that, when lies are self-promotional, lower power can be more corruptive than higher power.